Recent Insights into Osimertinib Analogues against EGFR Positive Non-small Cell Lung Cancer - Chhabra, Jatin; Kashyap, Priyanka; Pahwa, Rakesh; Narang, Rakesh; Dureja, Harish; Lal, Sukhbir; Verma, Sangeeta (Current Topics in Medicinal Chemistry, 2023)
Background: Lung cancer is a highly lethal malignancy with a poor prognosis and the leading cause of mortality worldwide. The development of mutations makes lung cancer treatment more challenging and expensive. Successful identification of epidermal growth factor receptor (EGFR) mutations led to the discovery of various third-generation tyrosine kinase inhibitors. Osimertinib is one of the promising and efficacious third-generation EGFR inhibitors and is mainly employed in the treatment of non-small cell lung cancer. Despite the initial effective response, osimertinib causes resistance in most of the patients after around 10 months of therapy, resulting in disease progression. To mitigate the effect of developed resistance, different osimertinib derivatives have been synthesized and evaluated by numerous research groups across the globe. Methods: Present article illustrates recent research advancements for the utilization of osimertinib and its derivatives in non-small cell lung cancer (NSCLC). Last seven years literature search has been conducted from PubMed, ScienceDirect, and Google Scholar databases, etc. Result: The present review emphasizes the recent advancements of osimertinib analogues that lead to enhanced antitumor potential and safety profile against non-small cell lung cancer. This manuscript also summarizes the different synthetic schemes involved in the synthesis of osimertinib analogues against EGFR reported by different research groups. Conclusion: Anticancer mechanistic insights, analytical prospects, drug interactions, pharmacokinetic considerations, and resistance profile of osimertinib are highlighted in the current manuscript.
Keywords: Osimertinib derivatives